IMPLEMENTASI TEKNIK CLUSTER PADA SCALETETRATONIK DAN PENTATONIK DALAM KARYAKARAKE’ DAN INANG - Arminandi, Juan; Mering, Aloysius; Indrapradja, Diecky K. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractFirst idea for make a music composition Karake? and Inang is a personal experience about dissimilarity. In music, dissmilarity is a very much like a scale. In music composition Karake Dan Inang use tetratonic and pentatonic scale with different instrument. Dissimilarity of the idea Karake? dan Inang use instrument West Borneo traditional like a dau. For westren instrument use vocal, clarinet in Bb and cello. Method and phase music composition Karake? dan Inang is a observation, eksploration, improvisation, formation of the music composition and evaluation for make easy steps. After find result of observation and eksploration,furthermore make a compisition technique. I make 3 music composition and the different is fundamental for compos the music. The  composition is use Kalimantan Barat traditional instrument and western instrument.Karake use Dau Traditional instrument, Karake use western instrument and Bakabon use mix traditional and western instrument. The Instrument just help composer for produce the sound, and not make we separate. Keyword: Cluster, Implementation,Karake? dan Inang, Scale